Space use and activity patterns of 3 species of diurnal small mammals in the Bangi Forest Reserve, UKM, Malaysia - Syakirah Samsudin,; Zubaid Akbar, (Universiti Kebangsaan Malaysia, 1997)
Space use and activity patterns by 3 species of small mammals, namely, Tupaia glis, Callosciurus notatus and e. nigrovitatus were determined. The home range size of T. glis ranged from 9,544 to 73,470m2, C. notatus from 6,512 to 16,150m2 and C. nigrovitatus 10,970m2. There was no overlap in the ranges between individuals of the same species and sex but the ranges of different species overlapped. There was no significant difference in the mean daily distance moved among the studied individuals. All individuals showed a bimodal type of activity pattern.